Hybrid Seed Production Using Cytoplasmic Male Sterile Lines in Cotton (Gossypium hirsutum L.) - WANG XUEDE; YAGYA DUTT; ZHAO XIANGQIAN (Seed Research, 2026)
The production of hybrid seed in cotton using CMS system requires adequate movement of fertile pollen from flower of restorer plant to flower of sterile plant. Natural transfer of pollen in cotton is not possible because pollen is heavy and sticky and not easy to be transferred by wind. Therefore, study on bee visiting and factors affecting the bee visit during pollination are essential in hybrid seeds production in cotton. The present study was conducted to find out the possible effect of total soluble sugar, sucrose and fructose content of different flower parts on the visiting frequency of honeybees and to analyze the relationship between the visit frequency of honeybee and yield of hybrid seed. The results shows that sucrose content in flowers especially in CMS flowers affected significantly to the honeybee population density and might be the key factor for higher hybrid seed production in some CMS (Kang-A and Y-11) and fertile lines. Thus, breeding male sterile lines with higher sugar content in flowers was propitious to the attraction of bee visiting, which could increase the rate of effective bolls per plant and decrease the rate of aborted seed and result higher yield of hybrid seed. Secondly, the mixed fashion method of seed production could be used to improve the bee visiting frequency. The mixed sowing fashion could shorten the distance of honeybee visiting flowers between restorer and sterile plants. Using indicative trait as marker, such as fiber or fuzz colour could make the mixed sowing fashion possible and effective, because hybrid seed could easily be picked out according to the indicative trait of the male sterile plants which will be different from restorer plants. Thus, cytoplasmic male sterility can be used effectively in cotton hybrid seed production, through developing a satisfactory restorer and a sterile line with higher sucrose content, and then application of a mixed planting method.